Psychoanalysis and Gender: current debates and new subjective constructions - Meler, Irene (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2020)
This paper give an account of the intersection between interdisciplinary gender studies and psychoanalytic theories about psyche and subjectivity. A exposition of different aspects in which female condition has been considered conceptually within the framework of various disciplinary perspectives that today, retrospectively, integrate a genealogy of feminisms that dialogue with the gender category and with psychoanalysis. After exploring the ambivalent and conflicting link between gender and psychoanalytic perspectives, an examination of the bonds between body, psyche and social condition of the subjects is offered.